2019
DOI: 10.1111/evo.13862
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary potential of an insect invader under climate change*

Abstract: Data <-read.table ('Qgen_CTL_TPC.txt', header=T, na.strings="NA") ##Loading pedigree Ped <-read.table('Pedigree.txt', header = TRUE, na.strings="NA") ##Create the inverse of the pedigree ainv <-asreml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 87 publications
1
36
3
Order By: Relevance
“…In many ways, variation in performance curves of N. crassa is quite typical for many ectotherms that have been studied (Sinclair et al ., 2016). Most genetic variation in N. crassa is variation in performance curve elevation, which contrasts with previous studies in other species that have found most variation to be for reaction norm shapes (Izem and Kingsolver, 2005; Logan et al ., 2019). Yet variation in tolerance curve elevation is commonly found, a review of thermal performance curves in insects found that elevation shifts were the most common type of change along environmental gradients (Tüzün and Stoks, 2018), see also Scheiner (1993).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In many ways, variation in performance curves of N. crassa is quite typical for many ectotherms that have been studied (Sinclair et al ., 2016). Most genetic variation in N. crassa is variation in performance curve elevation, which contrasts with previous studies in other species that have found most variation to be for reaction norm shapes (Izem and Kingsolver, 2005; Logan et al ., 2019). Yet variation in tolerance curve elevation is commonly found, a review of thermal performance curves in insects found that elevation shifts were the most common type of change along environmental gradients (Tüzün and Stoks, 2018), see also Scheiner (1993).…”
Section: Discussioncontrasting
confidence: 81%
“…In these studies, the genetic variance-covariance matrix (G-matrix) for thermal performance across several temperatures has been estimated, and how genetic variation is aligned with characteristic directions of reaction norm evolution has been determined (e.g. Izem and Kingsolver, 2005; Logan et al ., 2019). This is essential in order to explore how freely thermal performance can evolve in different environments, and to quantify if thermal performance evolution is bound to follow a certain evolutionary path or performance curve shape.…”
Section: Introductionmentioning
confidence: 99%
“…Canopy-dwelling tropical ants are known to behaviourally circumvent high temperature areas encountered while foraging, avoiding temperatures 5-10C below their thermal tolerance limits (Logan et al, 2019;Spicer et al, 2017). Thus, these butterflies and other high-altitude species must adapt their flying times and/or behaviours during hot periods, which could have cascading effects on fitness.…”
Section: Evidence Fo R Plasti CI Ty In He At Toler Ancementioning
confidence: 99%
“…Adaptation to novel niches has been widely studied in the context of invasive species that colonize and adapt to unfamiliar environments (Davis 2009, MacDougall et al 2009, Logan et al 2019). However, the ongoing refinement of traits that provide access to novel niches has received little attention, probably because most evolutionary novelties (and associated niche discoveries) occurred in the distant past and are therefore difficult to study.…”
Section: Introductionmentioning
confidence: 99%